2017
DOI: 10.3390/en10060791
|View full text |Cite
|
Sign up to set email alerts
|

Managing Traffic Flows for Cleaner Cities: The Role of Green Navigation Systems

Abstract: Cities worldwide suffer from serious air pollution problems and are main contributors to climate change. Green Navigation systems have a great potential to reduce fuel consumption and exhaust emissions from traffic. This research evaluates the impacts of different percentages of green drivers on traffic, CO 2 , and NO x over the entire Madrid Region. A macroscopic traffic model was combined with an enhanced macroscopic emissions model and a GIS (Geographic Information Systems) to simulate emissions on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…Table 6 shows the advantages and disadvantages of choosing different itineraries. These results obtained for a small city (Caceres) are similar to those obtained in a large city such as Madrid [38].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Table 6 shows the advantages and disadvantages of choosing different itineraries. These results obtained for a small city (Caceres) are similar to those obtained in a large city such as Madrid [38].…”
Section: Discussionsupporting
confidence: 84%
“…As for air pollution, pollutant emissions were reduced on urban routes by 35% on average. This result was higher than the savings reached in other green driving experiments, where in situations without important congestion levels, there were reductions of 13.8% and 20% [38,39]. However, if there is very high congestion, air pollutants could increase a lot, as reported by Bandeira et al [15] for CO (150%) and NOx (46%).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In line with this result, Kono et al [28] estimate that eco-route practice can reduce emissions by around 9% while increasing travel times by another 9%. Perez-Prada et al [29] evaluated the impacts of different percentages of eco-routing drivers on traffic, CO 2 , and NO x in the entire Madrid Region. The results showed reductions of up to 10.4% in CO 2 and 13.8% in NO x in congested traffic conditions with a 90% penetration of green drivers; however, the population's exposure to NO x increased by up to 20.2% as the results of eco-routing drivers choose a shorter route that has a higher population density.…”
Section: Eco-routingmentioning
confidence: 99%
“…Beyond the aforementioned four papers, there are also other interesting relevant studies that we have found and reviewed. For instance, the study in [16] (corresponding to Class II) conducts a thorough assessment of the impact of green navigation systems in a city's traffic flows, combining a macroscopic traffic model with a macroscopic emissions model and a GIS. Results show up to 10.4% reductions in CO 2 and up to 13.8% in NO x in congested traffic conditions for a 90% penetration of green drivers, but also that the overall population's exposure to NO x increases up to 20.2%.…”
Section: Related Workmentioning
confidence: 99%